The Influence of Price and Brand Image On Purchasing Interest in Skincare The Originote - Fadhila Turahmah Wijanarko; Sri Mulyono; Sulfarid Sulfarid (Universitas KH. Abdul Chalim Mojokerto, 2025)
The increasing interest in self-care, especially skincare, is characterized by the launch of new skincare products every year with different prices, quality and benefits, which has led to intense competition in the market. This condition leaves consumers with many choices and encourages companies to continue to innovate and create effective marketing plans to attract customers to make purchases. This research aims to explore how these two variables correlate with consumer intention to purchase The Originote skincare products, as they are important aspects in influencing consumer purchase intention. The research method used was a quantitative survey using a questionnaire to 96 respondents drawn using the Cochran formula to determine the sample size. The data obtained were analyzed using multiple linear regression with the help of SPSS 26 software. Price (X1) and brand image (X2) were found to have a positive and significant impact partially on the purchase intention of The Originote skincare products with a calculated t value of 4.151 and sig value. 0.000 for X1, and 8.305 with a sig value. 0.000 for X2. Thus, the most dominant aspect in influencing purchase intention is brand image. With a calculated f value of 95.144 and a sig value. 0.000, the price aspect and brand image have a joint (simultaneous) impact on buying interest in The Originote skincare products. Based on the results of the coefficient of determination (R2) test, 66.5% of buying interest is influenced by price and brand image variables, and the remaining 33.5% is influenced by other variables.